Airway Management Failure after Delayed Extubation in a Patient with Oral Malignant Melanoma Who Underwent Partial Mandibulectomy and Reconstruction with a Free Flap - Min A. Kwon; Jaegyok Song; Seokkon Kim; Pyeung-wha Oh; Minji Kang (Case Reports in Dentistry)
Maxillofacial surgery may cause severe complications in perioperative airway management. We report a case of failed airway management in a patient who underwent segmental mandibulectomy, radical neck dissection, and reconstruction with a free flap. The patient was extubated approximately 36 hours after surgery. Approximately 7 hours after extubation, the patient complained of dyspnoea, and respiratory failure followed. Bag-mask ventilation, direct laryngoscopy, video laryngoscopy, and supraglottic airway access were ineffective. The surgical airway was secured with an emergency tracheostomy while performing cardiopulmonary resuscitation. However, the patient experienced permanent hypoxic brain damage. The airway of patients with oral cancer may be compromised postoperatively due to surgical trauma and bulky flap reconstruction. Patients should be closely monitored during the postoperative period to prevent airway failure. Early diagnosis and airway management before airway failure occurs are important. Medical staff should be aware of airway management algorithms, be trained to perform difficult airway management, and have the required equipment readily available.